The role of nicotinamide adenine dinucleotide salvage enzymes in cardioprotection - Kibria, Fazle; Das, Sudip Kumar; Arefin, Md Sahidul (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2024)
The increasing trend of cardiac diseases is becoming a major threat globally. Cardiac activities are based on integrated action potential through electronic flux changes within intra- and extracellular molecular activities. Nicotinamide adenine dinucleotide (NAD) is a major electron carrier present in almost all living cells and creates gated potential by electron exchange from one chemical to another in terms of oxidation (NAD+) and reduction (NADH) reactions. NAD+ plays an important role directly or indirectly in protecting against various cardiovascular diseases, including heart failure, occlusion, ischemia-reperfusion (IR) injury, arrhythmia, myocardial infarction (MI), rhythmic disorder, and a higher order of cardiovascular complexity. Nicotinamide phosphoribosyl transferase (NAMPT) is well known as a rate-limiting enzyme in this pathway except for de-novo NAD synthesis and directly involved in the cardioprotective activity. There are two more enzymes – nicotinate phosphoribosyl transferase (NAPRT) and nicotinamide riboside kinase (NRK) – which also work as rate-limiting factors in the NAD+ synthesis pathway. This study concentrated on the role of NAMPT, NAPRT, and NRK in cardioprotective activity and prospective cardiac health.